2020
DOI: 10.7150/ijms.45470
|View full text |Cite
|
Sign up to set email alerts
|

Increased Proteinuria is Associated with Increased Aortic Arch Calcification, Cardio-Thoracic Ratio, Rapid Renal Progression and Increased Overall and Cardiovascular Mortality in Chronic Kidney Disease

Abstract: Background: Patients with chronic kidney disease (CKD) are associated with high prevalence rates of proteinuria, vascular calcification and cardiomegaly. In this study, we investigated relationships among proteinuria, aortic arch calcification (AoAC) and cardio-thoracic ratio (CTR) in patients with CKD stage 3A-5. In addition, we investigated correlations among proteinuria and decline in renal function, overall and cardiovascular (CV) mortality. Methods: We enrolled 482 pre-dialysis patients with CKD stage 3A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…23,24 Ogawa, Kauppila and Adragao scoring methods have been used successfully in assessing the progression of vascular calcification over time. 15,16,[25][26][27] The control subjects in the present study had less severe degree of hyperparathyroidism with lower serum calcium compared to the study group. This situation was inevitable since it was not possible to have patients with similar degree of hyperparathyroidism that had not undergone parathyroidectomy for a long period of time.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…23,24 Ogawa, Kauppila and Adragao scoring methods have been used successfully in assessing the progression of vascular calcification over time. 15,16,[25][26][27] The control subjects in the present study had less severe degree of hyperparathyroidism with lower serum calcium compared to the study group. This situation was inevitable since it was not possible to have patients with similar degree of hyperparathyroidism that had not undergone parathyroidectomy for a long period of time.…”
Section: Discussionmentioning
confidence: 52%
“…13,14 Ogawa scoring system has also been used successfully in assessing the progression of AoAC over time. 15,16 Briefly, AoAC score was determined using a circular scale with 16 circumferences that divided the aortic arch into 16 sections. Each section with calcification was counted and then combined yielding a final score ranging between 0 and 16.…”
Section: Determination Of Aortic Arch Calcificationmentioning
confidence: 99%
“…Высокая клиническая и прогностическая значимость альбуминурии не вызывает сомнения. Микроальбуминурия служит маркером повышенного риска сердечно-сосудистых событий, прогрессирующей ХБП и смерти от всех причин [15]. Взаимосвязь альбуминурии с такими общепринятыми маркерами сердечно-сосудистого риска, как АГ, СД и метаболический синдром, лишь частично объясняет ее негативное влияние на кардиоваскулярную систему.…”
Section: Discussionunclassified
“…Adeney et al demonstrated that even in patients with moderately advanced CKD (eGFR < 60 mL/min per 1.73 m 2 , mean 50.6 mL/min per 1.73 m 2 ) Shanahan without symptomatic cardiovascular disease (CVD), but with high serum phosphate level the prevalence and advancement of coronary artery calcification (CAC), calcification of descending aorta and mitral valve were significantly more pronounced as compared to subjects with normal kidney function [ 7 ]. Several studies reported the association between the risk of CV events and CV death and the degree of VC identified in several locations (coronary arteries, aortic arch and abdominal aorta) in different CKD patient groups (peritoneal dialysis, hemodialysis and pre-dialysis) [ 8 , 9 , 10 ]. The risk of cardiovascular and cerebrovascular events attributed to VC is largely independent from “traditional” risk factors for development of atherosclerosis, such as smoking, obesity or serum LDL-cholesterol [ 11 , 12 , 13 , 14 ].…”
Section: Introduction: Pathologic Calcification In Cardiovascular Systemmentioning
confidence: 99%